Analisis Kepuasan Masyarakat Terhadap Kehadiran Mal Pelayanan Publik (MPP) di Kota Bandung - Afifah, Zaidiah Nur; Rohimah, Nur Siti; Putra, Rizky Utama; Septiadi, Muhammad Andi (Universitas Airlangga, 2024)
The main focus that must be considered by the government is public satisfaction, which is reflected in the establishment of the Public Service Mall (MPP) as an effort to facilitate public access to administrative services. The purpose of this study is to identify the level of public satisfaction with the existence of MPP in Bandung City and analyze the factors that influence satisfaction. This research uses a mixed method, combining qualitative and quantitative methods. The results showed that the people of Bandung City were generally satisfied with the services provided, especially in terms of ease of procedures, speed of service time, fairness of tariffs, and comfort of facilities. The behavioral aspects of service officers related to friendliness and politeness also received high appreciation from the community. However, there are shortcomings, namely the inconsistency of employee attendance at MPP Bandung City. Evaluation continues to be carried out to ensure the improvement of public services in Bandung City. This study concludes that MPP Bandung City has met the standard indicators set out in Permen PAN Number 14 of 2017 by evaluating and continuously improving the aspects of service that are still lacking. This research contributes to improving public satisfaction, shows the importance of active community participation in service evaluation and improvement to improve the quality of public services in the future, and can also be a reference for other local governments that plan to implement MPP in their area. Keywords: Public Service Mall, Public Satisfaction, Service Quality